Heart Rate and Oxygen Uptake Kinetics in Type 2 Diabetes Patients – A Pilot Study on the Influence of Cardiovascular Medication on Regulatory Processes - Koschate, Jessica; Drescher, Uwe; Baum, Klaus; Brinkmann, Christian; Schiffer, Thorsten; Latsch, Joachim; Brixius, Klara; Hoffmann, Uwe (Experimental and Clinical Endocrinology & Diabetes, 2017)
The aim of this pilot study was to investigate whether there are differences in heart rate and oxygen uptake kinetics in type 2 diabetes patients, considering their cardiovascular medication. It was hypothesized that cardiovascular medication would affect heart rate and oxygen uptake kinetics and that this could be detected using a standardized exercise test. 18 subjects were tested for maximal oxygen uptake. Kinetics were measured in a single test session with standardized, randomized moderate-intensity work rate changes. Time series analysis was used to estimate kinetics. Greater maxima in cross-correlation functions indicate faster kinetics. 6 patients did not take any cardiovascular medication, 6 subjects took peripherally acting medication and 6 patients were treated with centrally acting medication. Maximum oxygen uptake was not significantly different between groups. Significant main effects were identified regarding differences in muscular oxygen uptake kinetics and heart rate kinetics. Muscular oxygen uptake kinetics were significantly faster than heart rate kinetics in the group with no cardiovascular medication (maximum in cross-correlation function of muscular oxygen uptake vs. heart rate; 0.32±0.08 vs. 0.25±0.06; p=0.001) and in the group taking peripherally acting medication (0.34±0.05 vs. 0.28±0.05; p=0.009) but not in the patients taking centrally acting medication (0.28±0.05 vs. 0.30±0.07; n.s.). It can be concluded that regulatory processes for the achievement of a similar maximal oxygen uptake are different between the groups. The used standardized test provided plausible results for heart rate and oxygen uptake kinetics in a single measurement session in this patient group.
Keywords: diabetes; hypertension; obesity